2008
DOI: 10.1007/s00431-008-0677-2
|View full text |Cite
|
Sign up to set email alerts
|

School functioning in 8- to 18-year-old children born after in vitro fertilization

Abstract: The aim of this study was to examine the school functioning of 8-to 18-year-old children born after in vitro fertilization (IVF). We compared 233 children born after IVF to 233 matched control children born spontaneously from parents with fertility problems on measures of education level, general cognitive ability, school performance (need for extra help, repeating a grade, special education), and rates of learning and developmental disorders. No differences were found between IVF and control children on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
(41 reference statements)
0
22
1
Order By: Relevance
“…However, natural multiple ovulation in older age is another reason for the increase in twinning rate since the mid-1980s as females have waited longer to start their families (Blondel and Kaminski, 2002), and it is most likely that only a small proportion of the twins in our sample had been born through in vitro fertilisation because the dramatic rise in its use took place in the 1990s (Herskind et al, 2005). In addition, no differences were found in studies comparing cognitive development and school performance in IVF and naturally conceived children, controlling for parental education (Mains et al, 2010; Wagenaar et al, 2008). …”
Section: Discussionmentioning
confidence: 91%
“…However, natural multiple ovulation in older age is another reason for the increase in twinning rate since the mid-1980s as females have waited longer to start their families (Blondel and Kaminski, 2002), and it is most likely that only a small proportion of the twins in our sample had been born through in vitro fertilisation because the dramatic rise in its use took place in the 1990s (Herskind et al, 2005). In addition, no differences were found in studies comparing cognitive development and school performance in IVF and naturally conceived children, controlling for parental education (Mains et al, 2010; Wagenaar et al, 2008). …”
Section: Discussionmentioning
confidence: 91%
“…It should be realized, however, that epilepsy and febrile seizures are specific neurologic entities, whereas the quality of GMs is a parameter of general neurologic function. Wagenaar et al (50,51) reported on school functioning, behavior, and socioemotional functioning of 9-18-year old IVF children. School functioning was similar; however, IVF children were found to show fewer problem behavior and attention problems but more withdrawn or depressed behavior compared with children of subfertile parents.…”
Section: Infants Of Subfertile Couplesmentioning
confidence: 98%
“…However, the overwhelming majority of the studies on the neurodevelopment of children born at full term after ART consistently show that these children are in a comparable condition to NC children (Källén et al, 2005;Ponjaert-Kristoffersen et al, 2005;Leunens et al, 2006;Wagenaar et al, 2008;2009b;Hvidtjørn et al, 2009;Carson et al, 2010;Mains et al, 2010;Tsai et al, 2011). The follow-up studies have all focused on kids and adolescents through 18 years of age because of the short duration of ART's history.…”
Section: Neurological and Neurodevelopmental Outcomesmentioning
confidence: 99%